Prevalence of Antimicrobial-Resistant Pathogens in Canadian Hospitals: Results of the Canadian Ward Surveillance Study (CANWARD 2007). (2009) - Zhanel, George G; Karlowsky, James A; DeCorby, Mel; Nichol, Kim A; Wierzbowski, Aleksandra; Baudry, Patricia J; Lagacé-Wiens, Philippe; Walkty, Andrew; Schweizer, Frank; Adam, Heather; McCracken, Melissa; Mulvey, Michael R; et al.
Abstract : BACKGROUND: Canadian hospitals as well as hospitals worldwide are increasingly faced with antibiotic-resistant pathogens, including multidrug-resistant (MDR) strains. OBJECTIVES: To assess the prevalence of pathogens, including the resistance genotypes of methicillin-resistant Staphylococcus aureus (MRSA), vancomycin-resistant enterococci (VRE) and extendedspectrum beta-lactamase (ESBL)-producing Escherichia coli in Canadian hospitals, as well as their antimicrobial resistance patterns. MEtHODS: Bacterial isolates were obtained between January 1, 2007, and December 31, 2007, inclusive, from patients in 12 hospitals across Canada as part of the Canadian Ward Surveillance Study (CANWARD 2007). Isolates were obtained from bacteremic, urinary, respiratory and wound specimens and underwent antimicrobial susceptibility testing. Susceptibility testing was assessed using the Clinical and Laboratory Standards Institute broth microdilution method. RESULTS: In total, 7881 isolates were recovered from clinical specimens of patients attending Canadian hospitals. The 7881 isolates were collected from respiratory (n=2306; 29.3%), blood (n=3631; 46.1%), wounds/tissue (n=617; 7.8%) and urinary (n=1327; 16.8%) specimens. The 10 most common organisms isolated from 76.5% of all clinical specimens were E coli (21.6%), methicillin-susceptible S aureus (13.9%), Streptococcus pneumoniae (8.9%), Pseudomonas aeruginosa (8.0%), Klebsiella pneumoniae (5.8%), MRSA (4.9%), Haemophilus influenzae (4.3%), coagulase-negative staphylococci/ taphylococcus epidermidis S (4.0%), Enterococcus species (3.0%) and Enterobacter cloacae (2.1%). MRSA made up 26.0% (385 of 1480) of all S aureus (genotypically, 79.2% of MRSA were health care-associated MRSA and 19.5% were community-associated MRSA), and VRE made up 1.8% of all enterococci (62.5% of VRE had the van A genotype). ESBLproducing E coli occurred in 3.4% of E coli isolates. The CTX-M type was the predominant ESBL, with CTX-M-15 as the predominant genotype. With MRSA, no resistance was observed to daptomycin, linezolid, tigecycline and vancomycin, while resistance rates to other agents were: clarithromycin 91.4%, clindamycin 61.8%, fluoroquinolones 88.6% to 89.6%, and trimethoprim-sulfamethoxazole 12.2%. With E coli, no resistance was observed to ertapenem, meropenem and tigecycline, while resistance rates to other agents were: amikacin 0.1%, cefazolin 14.2%, cefepime 2.0%, ceftriaxone 8.9%, gentamicin 10.6%, fluoroquinolones 23.6% to 24.5%, piperacillin-tazobactam 1.3% and trimethoprim-sulfamethoxazole 26.6%. Resistance rates with P aeruginosa were: amikacin 7.6%, cefepime 11.7%, gentamicin 20.8%, fluoroquinolones 23.4% to 25.1%, meropenem 8.1% and piperacillin- tazobactam 7.3%. A MDR phenotype (resistance to three or more of cefepime, piperacillin-tazobactam, meropenem, amikacin or gentamicin, and ciprofloxacin) occurred frequently in P aeruginosa (10.6%) but uncommonly in E coli (1.2%), K pneumoniae (1.5%), E cloacae (0%) or H influenzae (0%). CONCLUSIONS: E coli, S aureus (methicillin-susceptible and MRSA), S pneumoniae, P aeruginosa, K pneumoniae, H influenzae and Enterococcus species are the most common isolates recovered from clinical specimens in Canadian hospitals. The prevalence of MRSA was 26.0% (of which genotypically, 19.5% was community-associated MRSA), while VRE and ESBL-producing E coli occurred in 1.8% and 3.4% of isolates, respectively. A MDR phenotype is common with P aeruginosa in Canadian hospitals.